Resilience of Breeding Boreal Waterbirds to Harsh Wintering Conditions: Could Climate Warming Smooth Population Declines? - Pöysä, Hannu; Lammi, Esa; Väänänen, Veli-Matti (My University, 2026)
Due to global climate change, winters have become milder and the ice season in lakes and other aquatic systems shorter across the Northern Hemisphere. Consequently, wintering conditions of open water-dependent waterbirds have become milder. While winter warming-caused changes in the distribution of wintering waterbirds have been documented for several species, it is unclear how warming of winters is reflected in population dynamics and long-term trends of waterbirds in northern breeding areas. We used population count data and studied resilience (resistance to cold winters and recovery thereafter) of 15 waterbird species breeding in European boreal lakes to harsh wintering conditions during 1977–2022. Our aim was to assess the possibility that climate warming could smooth observed waterbird population declines caused by other anthropogenic stressors. In general, wintering conditions had only marginal impact on the dynamics (growth rate) of waterbird populations, except in the Common Coot (Fulica atra), in which cold winters affected population growth rate negatively. Even though population growth rate of most species was relatively resistant to cold winters, population trajectories of six species showed evidence of increase after a period of three consecutive exceptionally cold winters, suggesting high recovery rate. We found no evidence of association between resistance to cold winters and body size and species' thermal niches in their wintering ranges or between recovery rate and life history variables (clutch size and age at 1st reproduction). Nor did we find evidence of association between resistance to cold winters and long-term population trend. Our results suggest that most waterbird species do not benefit from warming winters because their breeding populations appeared to be relatively unresponsive to variation in winter weather conditions. Hence, warmer winters may not provide a mechanism that could mitigate negative impacts of other anthropogenic stressors on breeding populations of waterbirds in northern Europe.
Keywords: breeding waterbirds; climate change; extreme events; long-term population trends; population dynamics; population resilience